Understanding the Link Between Maternal Overnutrition, Cardio-Metabolic Dysfunction and Cognitive Aging - Peleg-Raibstein, Daria (Frontiers in Neuroscience, 2021)
Obesity has long been identified as a global epidemic with major health implications such as diabetes and cardiovascular disease. Maternal overnutrition leads to significant health issues in industrial countries and is one of the risk factors for the development of obesity and related disorders in the progeny. The wide accessibility of junk food in recent years is one of the major causes of obesity, as it is low in nutrient content and usually high in salt, sugar, fat, and calories. An excess of nutrients during fetal life not only has immediate effects on the fetus, including increased growth and fat deposition in utero, but also has long-term health consequences. Based on human studies, it is difficult to discern between genetic and environmental contributions to the risk of disease in future generations. Consequently, animal models are essential for studying the impact of maternal overnutrition on the developing offspring. Recently, animal models provided some insight into the physiological mechanisms that underlie developmental programming. Most of the studies employed thus far have focused only on obesity and metabolic dysfunctions in the offspring. These studies have advanced our understanding of how maternal overnutrition in the form of high-fat diet exposure can lead to an increased risk of obesity in the offspring, but many questions remain open. How maternal overnutrition may increase the risk of developing brain pathology such as cognitive disabilities in the offspring and increase the risk to develop metabolic disorders later in life? Further, does maternal overnutrition exacerbate cognitive- and cardio-metabolic aging in the offspring?